ROLE OF SOME MICRONUTRIENTS IN THE HEALING PROCESS OF DIABETIC ULCERS - Minka Hristova; Antoniya Hachmeriyan (Journal of IMAB)
Background: Diabetic foot ulcer (DFU) is among the most serious and traumatic complications of diabetes mellitus. Nutrition is essential in chronic wound healing as extra nutrients, including micronutrients, are often needed for proper tissue repair. We aim to examine and analyze the relationship between oral intake of some micronutrients and wound healing in patients with DFU. Methods: A search was conducted in the Medline/Pubmed and Google Scholar databases, using comprehensive keywords, and articles published in the last 10 years were analyzed. Review Results: Minerals represent an essential factor in the multifaceted wound healing process. Micronutrient deficiency affects all phases of wound healing, including collagen synthesis, fibroblast proliferation, and epithelization. Magnesium, zinc, selenium, and copper have been postulated as beneficial for DFU as they function as antioxidants modulate immunity, cell replication and differentiation, and tissue repair. Conclusion: More research is needed to clarify and warrant the use of mineral supplementation for the prevention and healing of diabetic foot ulcers.